AN ANALYSIS OF THE CULTURALLY-BOUND EXPRESSIONS IN THE ENGLISH TRANSLATION VERSION OF AHMAD TOHARI’S RONGGENG DUKUH PARUH - Rini, Yulan Puspita (Universitas Islam Negeri Raden Intan Lampung, 2013)
This study aims at identifying the culturally-bound expressions in the Englishtranslation version of Ahmad Tohari’s Ronggeng Dukuh Parukin terms of techniques totranslate the culturally-bound expressions and their meaning equivalence.This study uses a qualitative approach. The objects of this study are culturally-bound expressions in the form of words, phrases and clauses. The researcher becomes the primary instrument of this study. The secondary instrument is data sheets. In translating the culturally-bound expressions, the translator uses five techniques to solve the cultural gap between the source and target languages. The techniques can bridge the cultural gap